Geometry in Iranian Painting as Sacred Art in the Works of Kamal al-Din Bihzad - Ali Ghashghaei; Hosein Ardalani (نگره, 2021)
In this article, we will discuss the art of painting in Herat School. In fact, the head of painters in this school is Kamal al-Din Bihzad. So we will consider his works and his style in a contextual way and find the sacred art in his paintings. What is discussed here is the geometry used in the works of Kamal al-Din Bihzad who used geometric motifs in order to manifest spirituality in a direct way. This paper is based on descriptive-deductive and library research methods. This article examines the geometric patterns in the works of Kamal al-Din Bihzad, then compares them together, and subsequently reaches a general conclusion, so it proves the hypothesis. From this point of view, this descriptive-analytical research is based on adaptational and inductive approaches. The statistical population includes seven examples of paintings by Bihzad or attributed to Bihzad. Another methodology that is discussed in this research, examines the geometry used in the drawings, which are matched in the framework of this article. As a result of these comparisons, drawings are revealed to be centered on the concept of divinity, due to the geometry of the designs. Therefore, these images are the subject of the research question of this research.This study works on seven paintings made by or attributed to Kamal al-Din Bihzad, comparing the elements used in these works with their counterparts in architectural buildings. We study on repetition of the geometric patterns used in the architectural spaces of Bihzad's paintings. The view based on this article is a traditionalist view. This means that the views of the Western and the Eastern philosophers with regard to revival of the unity of meanings are taken into account in answering the questions of this research. In other words, we consider the traditionalist idea, the source of which is the proof of the essence of the divine sanctuary, which sees the source of survival in annihilation and the everlasting and eternal nature in the unity of meanings, as one of the main aspects of this research. Another theoretical aspect that was necessary in this research is the view of mystics towards art and beauty. This approach is discussed in this article because part of the traditionalist view is based on the views of the mystics who existed before the emergence of the philosophy of traditionalism and influenced the space around them under a special system. Taken together, all logical theories and hypotheses of this research have been proven regarding the main question of the research that is based on this point that to what extent has Bihzad used geometric motifs in his paintings? In which of Bihzad's paintings does the geometry of the motifs act independently and is visually expressed as an independent form to show the essence of the sacred divinity? The main emphasis of this discussion will be on the paintings of "Joseph Escaping Zuleikha" and "Prophet Mohammad (PBUH) and His Companions".As a result, Kamal al-Din Bihzad's works can be divided into two categories in terms of the necessity of applying the geometry of patterns in them: 1- Works in which the geometry of patterns is discussed as an independent unit; 2- Works where the geometry of the motifs has appeared in order to decorate the drawings.To answer the research questions of this article, we found out that each painting with a divine or mystical theme is considered as sacred art and it is full of geometric patterns. The first category focuses on the works that prove the theory of this article, in which Bihzad deals with the geometry of the motifs as an independent unit, in works such as "Joseph Escaping Zuleikha" and "Prophet Mohammad (PBUH) and His Companions". These paintings are full of geometric motifs and it is directly derived from architecture, because if we remove the architectural plan, we find out that the visual expression is not damaged. Geometry takes steps to elevate the textual meaning of the image.But the second category includes works in which the geometry of the motifs is more considered in terms of the decorative aspect of architecture and is used to make the architectural building look magnificent. The purpose of applying the geometry of the designs was to make it glorious. So In these paintings, geometry is related to architecture and it seems that it has a decorative aspect in terms of the glory of the palace and has found an auxiliary role for architecture.